Minor role of mature adipocyte mineralocorticoid receptor in high-fat diet-induced obesity. Issue 2 (November 2018) - Feraco, A; Armani, A; Urbanet, R; Nguyen Dinh Cat, A; Marzolla, V; Jaisser, F; Caprio, M
Abstract : Obesity is a major risk factor that contributes to the development of cardiovascular disease and type 2 diabetes. Mineralocorticoid receptor (MR) expression is increased in the adipose tissue of obese patients and several studies provide evidence that MR pharmacological antagonism improves glucose metabolism in genetic and diet-induced mouse models of obesity. In order to investigate whether the lack of adipocyte MR is sufficient to explain these beneficial metabolic effects, we generated a mouse model with inducible adipocyte-specific deletion of Nr3c2 gene encoding MR (adipo-MRKO). We observed a significant, yet not complete, reduction of Nr3c2 transcript and MR protein expression in subcutaneous and visceral adipose depots of adipo-MRKO mice. Notably, only mature adipocyte fraction lacks MR, whereas the stromal vascular fraction maintains normal MR expression in our mouse model. Adipo-MRKO mice fed a 45% high-fat diet for 14 weeks did not show any significant difference in body weight and fat mass compared to control littermates. Glucose and insulin tolerance tests revealed that mature adipocyte MR deficiency did not improve insulin sensitivity in response to a metabolic homeostatic challenge. Accordingly, no significant changes were observed in gene expression profile of adipogenic and inflammatory markers in adipose tissue of adipo-MRKO mice. Moreover, pharmacological MR antagonism in mature primary murine adipocytes, which differentiated ex vivo from WT mice, did not display any effect on adipokine expression. Taken together, these data demonstrate that the depletion of MR in mature adipocytes displays a minor role in diet-induced obesity and metabolic dysfunctions.